SINKRONISASI KONDISI INTERNAL DAN TREN EKSTERNAL PADA PERENCANAAN JANGKA PANJANG ORGANISASI PUBLIK - Rahayu Mardikaningsih; Aulia Salsabillah Az-Zahro; Nazwa Nurul Izzah; Didit Darmawan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This conceptual study examines how internal and external analysis integration supports long term planning for public sector organizational sustainability. Findings reveal that integration requires systematic procedures: internal factor identification covering fiscal capacity, personnel competence, technology infrastructure, and bureaucratic culture; external factor identification covering demograp hic trends, economic conditions, technological advances, and regulato ry changes; cross mapping between both factor groups; translation into strategic options; and periodic review mechanisms. Cross mappi ng generates four strategy types: offensive for strength opportunity conditions, defensive for threat weakness conditions, turnaround for opportunity weakness conditions, and survival for threat weakness conditions. Sustainability encompasses three dimensions: fiscal sustai nability, institutional sustainability, & program sustainability. Public participation & organizational learning culture determine integration success.